Manajemen risiko sebagai kunci keberlangsungan perbankan syariah di Indonesia - Rohim, Muhammad (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the role of risk management in Sharia Banking Planning, which is very important in managing unique risks related to sharia principles. The research method used is a literature review from relevant sources related to risk management in sharia banking planning by outlining the important steps in risk management, including identification, assessment, control and monitoring of risks such as usury risk, operational risk and market risk in the context of sharia banking in Indonesia. The results of this research are that sharia financial institutions can maintain the continuity of their operations in accordance with sharia principles while increasing their integrity in providing financial services in accordance with sharia values ​​by identifying, assessing, controlling and monitoring future risks.